Novel solar light driven photocatalyst, zinc indium vanadate for photodegradation of aqueous phenol - Mahapure, Sonali A.; Rane, Vilas H.; Ambekar, Jalindar D.; Nikam, Latesh K.; Marimuthu, R.; Kulkarni, Milind V.; Kale, Bharat B. (Materials Research Bulletin, 2011)
In the present investigation, we have demonstrated the synthesis of novel photocatalyst, zinc indium vanadate (ZIV) by solid solid state route using respective oxides of zinc, indium and vanadium. This novel photocatalyst was characterized using XRD, FESEM, UV-DRS and FTIR in order to investigate its structural, morphological and optical properties. XRD clearly shows the formation of phase pure ZIV of triclinic crystal structure with good crystallinity. FESEM micrographs showed the clustered morphology having particle size between 0.5 and 1 mu m. Since, optical study showed the band gap around 2.8 eV, i.e. in visible region, we have performed the photocatalytic activity of phenol degradation under visible light irradiation. The photodecomposition of phenol by ZIV is studied for the first time and an excellent photocatalytic activity was obtained using this novel photocatalyst. Considering the band gap of zinc indium vanadate in visible region, it will also be the potential candidate for water splitting. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Chemical synthesis; Oxides; X-ray diffraction

Morphology controlled synthesis of LiV(2)0(5)/Ag nanocomposite nanotubes with enhanced electrochemical performance - Diggikar, Rahul S.; Dhavale, Vishal M.; Shinde, Dhanraj B.; Kanbargi, Nihal S.; Kulkarni, Milind V.; Kale, Bharat B. (RSC Advances, 2012)
Uniformly embedded silver (Ag) nanoparticles in orthorhombic nanotubes (NTs) of lithium vanadium oxide (LVO) synthesized via a facile template-free hydrothermal treatment at low temperature exhibited an excellent morphology with good crystallinity and may act as an exceptional contender for electronic applications.

Nanowires of silver-polyaniline nanocomposite synthesized via in situ polymerization and its novel functionality as an antibacterial agent - Tamboli, Mohaseen S.; Kulkarni, Milind V.; Patil, Rajendra H.; Gade, Wasudeo N.; Navale, Shalaka C.; Kale, Bharat B. (Colloids and Surfaces B-Biointerfaces, 2012)
Silver-polyaniline (Ag-PANI) nanocomposite was synthesized by in situ polymerization method using ammonium persulfate CAPS) as an oxidizing agent in the presence of dodecylbenzene sulfonic acid (DBSA) and silver nitrate (AgNO3). The as synthesized Ag-PANI nanocomposite was characterized by using different analytical techniques such as UV-visible (UV-vis) and Fourier transform Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), thermo gravimetric analysis (TGA). X-ray diffraction (XRD), and transmission electron microscopy (TEM). UV-visible spectra of the synthesized nanocomposite showed a sharp peak at similar to 420 nm corresponding to the surface plasmon resonance (SPR) of the silver nanoparticles (AgNPs) embedded in the polymer matrix which is overlapped by the polaronic peak of polyaniline appearing at that wavelength. Nanowires of Ag-PANI nanocomposite with diameter 50-70 nm were observed in FE-SEM and TEM. TGA has indicated an enhanced thermal stability of nanocomposite as compared to that of pure polymer. The Ag-PANI nanocomposite has shown an antibacterial activity against model organisms, a gram positive Bacillus subtilis NCIM 6633 in Mueller-Hinton (MH) medium, which is hitherto unattempted. The Ag-PANI nanocomposite with monodispersed AgNPs is considered to have potential applications in sensors, catalysis, batteries and electronic devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Conducting poly(aniline); In situ polymerization; Nanocomposite

Nanostructured 2D MoS2 honeycomb and hierarchical 3D CdMoS4 marigold nanoflowers for hydrogen production under solar light - Kadam, Sunil R.; Late, Dattatray J.; Panmand, Rajendra P.; Kulkarni, Milind V.; Nikam, Latesh K.; Gosavi, Suresh W.; Park, Chan J.; Kale, Bharat B. (Journal of Materials Chemistry A, 2015)
Unique two dimensional (2D) honeycomb layered MoS2 nanostructures and hierarchical 3D marigold nanoflowers of CdMoS4 were designed using a template free and facile solvothermal method. The MoS2 structure is depicted with a sheet like morphology with lateral dimensions of 5-10 mu m and a thickness of similar to 200 nm and a honeycomb nanostructure architecture produced via the self-assembling of vertically grown thin hexagonal nanosheets with a thickness of 2-3 nm. The 3D CdMoS4 marigold nanoflower architecture comprised thin nanopetals with lateral dimensions of 1-2 mu m and a thickness of a few nm. The CdMoS4 and MoS2 structures displayed hydrogen ( H-2) production rates of 25 445 and 12 555 mu mol h(-1) g(-1), respectively. The apparent quantum yields of hydrogen production were observed to be 35.34% and 17.18% for CdMoS4 and MoS2, respectively. The 3D nanostructured marigold flowers of CdMoS4 and honeycomb like 2D nanostructure of MoS2 were responsible for higher photocatalytic activity due to inhibition of the charge carrier recombination. The prima facie observation of H-2 production showed that the ternary semiconductor confers enhanced photocatalytic activity for H-2 generation due to its unique structure. Such structures can be designed and implemented in other transition metal dichalcogenide based ternary materials for enhanced photocatalytic and other applications.